The Relationship Between Watching Violence in Mass Media and Aggressive Behavior of Students at SMK N 9 Padang " - Fatzki Vostoka Ummai; Mursyid Ridha (Jurnal Neo Konseling, 2019)
Mass media is a tool used in delivering messages from sources to the public (recipients) using mechanical communication tools such as newspapers, films, radio and television. Aggression behavior in the educational environment lately occurs a lot in the elementary school environment. One reason is the exposure of mass media that display violence. Students who often watch television shows on television can cause a tendency for aggression to emerge. The purpose of this study was to determine the relationship between watching violent acts in the mass media with the aggressive behavior of school students. based on the results indicated by a significant number of 0.014 which means that less than 5% or the relationship between watching acts of violence in the mass media with aggressive behavior of students there is a significant or significant relationship that is equal to 18%. If an equation is made, namely Y = 164,303 + 0.597 X it means that if given treatment is improved watching violence in the mass media by 1 unit there will be an increase in the aggressive behavior of students by 0.597 units.